Samnyong the mute = 벙어리 삼룡이 - Na, To-hyang 1902-1927 (바이링궐 에디션 한국 대표 소설, 2015)
Samnyong is a typical subaltern in Chosǒn during Japan's colonial period - a character robbed of his voice. The story's literary achievement lies in the process in which the subaltern's repressed sexual desire blooms, while his rage at the class system explodes.